1972
DOI: 10.1039/c39720001253
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the tetranortriterpene bussein

Abstract: Bussein is shown to be a mixture of bussein A, C44H56018, and bussein B, C,,H,O,, ; structure (Ia) is proposed for bussein A and structure (Ib) for bussein B.caudatum Sprague,l and has been concluded to contain, among others, three acetyl, one isobutyryl, and one 2-methylbutyryl g r o u ~s . ~, ~We have found that bussein is a mixture of two components, i.e. bussein A, C,H,,O,,, and bussein B, C4,HM01,, to which structures (Ia) and (Ib), respectively, are assigned. The mass spectrum of a crystalline sample, BU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…We are only aware of one earlier calculation of vibrational corrections to noble gas dimer chemical shifts, a CCSD calculation on Xe 2 . [24] Their averaged CCSD value for the dimer shift, 29.93 ppm, is in very good agreement with our value 30.30 ppm.…”
Section: Zero-point Vibrational Correctionssupporting
confidence: 86%
See 2 more Smart Citations
“…We are only aware of one earlier calculation of vibrational corrections to noble gas dimer chemical shifts, a CCSD calculation on Xe 2 . [24] Their averaged CCSD value for the dimer shift, 29.93 ppm, is in very good agreement with our value 30.30 ppm.…”
Section: Zero-point Vibrational Correctionssupporting
confidence: 86%
“…Comparison of our CCSD(T) results with literature values [12,16,21,[23][24][25][26] obtained at the CCSD or higher levels but with different one-electron basis sets and sometimes at slightly different equilibrium geometries shows excellent agreement.…”
Section: Electron Correlation Effectssupporting
confidence: 76%
See 1 more Smart Citation
“…The C-15-acyl 16-norphragmalins isolated in this investigation and reported previously [11][12][13][14] could be correlated well by the plausible biosynthetic pathway, and we think that the origin of carbonate moiety in 16-norphragmalin limonoids (1)(2)(3)(4)(5)(6)(7)(8) maybe comes from the 16-carbonyl of phragmalin skeleton which degradated through decarboxylation. Herein, the isolation, structural elucidation, the anti-inflammatory activity, as well as the proposed biosynthetic pathway of these novel compounds were reported.…”
mentioning
confidence: 93%
“…Numerous computational studies on 129 Xe NMR properties have been reported for molecules containing Xe [30][31][32][33][34][35] as well as for Xe atom guest-host systems. [33,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] In this article, we study the 129 Xe CS of endohedral Xe atom in Xe@C 60 molecule with particular aim at faithful simulations of experimental conditions and assessment of the different physical contributions to the experimental 129 Xe NMR CS, such as relativistic, dynamic, and solvent effects.…”
Section: Introductionmentioning
confidence: 99%